Exploring the relationships between soundscape quality and public health using a systems thinking approach - Aletta, Francesco (2025)
Urban soundscapes significantly influence public health, with sound quality affecting well-being and social value. While traditional noise control has emphasized harm reduction, soundscape studies propose that managing sound environments can promote health benefits. This study explores the complex relationships between soundscape quality and public health using a systems thinking approach. In a participatory workshop with 21 experts from fields such as urban planning, environmental psychology, and acoustics, a causal loop diagram (CLD) was developed to illustrate the interactions between soundscape quality and public health variables. The CLD revealed key feedback loops and intervention points, organized around themes of socio-economic impact, environmental justice, biodiversity, and soundscape design. Findings highlight that while soundscape quality can enhance community well-being, increased economic value may drive gentrification, altering the social structure and reducing sound source diversity. Additionally, the role of soundscape quality in biodiversity suggests both co-benefits and ecological risks. This study demonstrates the potential of systems thinking to guide interdisciplinary approaches in soundscape management, identifying strategic pathways to inform future research and policy development for equitable and health-promoting urban environments.